2017
DOI: 10.1051/rees/2017032
|View full text |Cite
|
Sign up to set email alerts
|

Determining the performance of a Diffuser Augmented Wind Turbine using a combined CFD/BEM method

Abstract: Abstract. Traditionally, the optimisation of a Diffuser Augmented Wind Turbine has focused on maximising power output. However, due to the often less than ideal location of small-scale turbines, cut-in speed and starting time are of equal importance in maximising Annual Energy Production, which is the ultimate goal of any wind turbine design. This paper proposes a method of determining power output, cut-in speed and starting time using a combination of Computational Fluid Dynamics and Blade Element Momentum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Laboratory measurements showed that improvements were obtained on electrical output, resulting in a maximum increase of 120 %. Measurements showed a power augmentation by a factor about 1.5-2.3, compared with the rotor without the shroud [28]. Therefore augmentation device/ diffuser concept can offer several benefits in the future electrical generation.…”
Section: Introductionmentioning
confidence: 97%
“…Laboratory measurements showed that improvements were obtained on electrical output, resulting in a maximum increase of 120 %. Measurements showed a power augmentation by a factor about 1.5-2.3, compared with the rotor without the shroud [28]. Therefore augmentation device/ diffuser concept can offer several benefits in the future electrical generation.…”
Section: Introductionmentioning
confidence: 97%
“…Hansen [8]. The diffuser can be modeled using computational fluid dynamics (CFD), e.g, [3] and Kesby et al [9], and, clearly, its performance is influenced by interaction with the blades. If CFD is not used, it is often assumed that the diffuser is perfectly efficient, although methods to include finite efficiency have been available for a long time, e.g.…”
Section: Introductionmentioning
confidence: 99%